1978
DOI: 10.1002/bjs.1800650323
|View full text |Cite
|
Sign up to set email alerts
|

The nature of hypocalcaemia in acute pancreatitis

Abstract: A retrospective and prospective study was made of 82 attacks of acute pancreatitis occurring in 80 patients. Attacks were defined as mild (55) or severe (27) according to clinical criteria. Severe attacks were associated with significantly low levels of uncorrected calcium and calculated ionized calcium, both at the time of admission and 48 h later. Patients with severe attacks were found to have lower levels of parathyroid hormone than either those with mild attacks or other patients who had undergone an abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
1
3

Year Published

1978
1978
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 13 publications
0
17
1
3
Order By: Relevance
“…In contrast, our findings are at variance with those of investigators who found low PTH levels in patients with acute pancreatitis, especially in cases with hypocalcaemia and more severe forms of the disease (Condon et al, 1975;Robertson et al, 1976;McMahon et al, 1978). Some of these workers (Condon et al, 1975) suggested that supplementary PTH might be given to patients with pancreatitis and hypocalcaemia, but we would contend, on the basis of the data presented, that this would be very rarely, if ever, justifiable or necessary.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In contrast, our findings are at variance with those of investigators who found low PTH levels in patients with acute pancreatitis, especially in cases with hypocalcaemia and more severe forms of the disease (Condon et al, 1975;Robertson et al, 1976;McMahon et al, 1978). Some of these workers (Condon et al, 1975) suggested that supplementary PTH might be given to patients with pancreatitis and hypocalcaemia, but we would contend, on the basis of the data presented, that this would be very rarely, if ever, justifiable or necessary.…”
Section: Discussioncontrasting
confidence: 88%
“…THE levels of parathyroid hormone (PTH) have been measured in the blood of patients with acute pancreatitis by several teams of investigators, with conflicting results. Some have reported low PTH levels associated with hypocalcaemia (Condon et al, 1975;Robertson et al, 1976;McMahon et al, 1978), while others described high levels of PTH and a significant inverse correlation with serum ionized calcium levels (Weir et al, 1975). A small number of patients were studied in each of these four reports, and in very few were sequential measurements of PTH levels recorded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Edmondson and Berne (4) found that patients with severe pancreatitis developed low serum calcium levels, and the association between hypocalcaemia and severity has been verified by more recent reports (2,5,6).…”
mentioning
confidence: 69%
“…12,13 Proposed mechanisms for hypocalcaemia in early phase are autodigestion of mesenteric fat by pancreatic enzymes and release of free fatty acids, which form calcium salts, transient hypoparathyroidism, and hypomagnesemia. [14][15][16] Later stages of pancreatitis are frequently complicated by sepsis. Whitted et al proposed that increased circulating catecholamines in sepsis cause a shift of circulating calcium into the intracellular compartment, leading to relative hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%